Fertilization mode differentially impacts the evolution of vertebrate sperm components - Ariel F. Kahrl; Rhonda R. Snook; John L. Fitzpatrick (Nature Communications, 2022)
The location where fertilization takes place can be highly variable across species, and especially between internal and external fertilizers. Kahrl et al. find that fertilization environment plays a significant role in the evolution and diversification of sperm morphology across vertebrate species.